Designing, developing, and facilitating smart cities : urban design to IoT solutions - Angelakis, Vangelis; Tragos, Elias; Pöhls, Henrich C.; Kapovits, Adam; Bassi, Alessandro (Springer, 2016)
This book discusses how smart cities strive to deploy and interconnect infrastructures and services to guarantee that authorities and citizens have access to reliable and global customized services.
Keywords: City planning -- Technological innovations.; Internet of things.; elektronické knihy; electronic books